The Effect of Employee Empowerment, Intellectual Intelligence, and Interpersonal Communication on the Performance of Civil Servants - Wildan Sholahudin Al-Ayubi; Muhamad Alwi (Greenation Research & Yayasan Global Resarch National, 2026)
This study is motivated by the suboptimal performance of civil servants in delivering public services. The objective of this study is to analyze the effect of employee empowerment, intellectual intelligence, and interpersonal communication on the performance of civil servants. The research object consists of civil servants working in several government agencies in Majalengka Regency. This research employs a quantitative method with data collected through questionnaires distributed to all 60 respondents. Data analysis was conducted using multiple linear regression analysis. The results indicate that employee empowerment has a positive and significant effect on the performance of civil servants. Meanwhile, intellectual intelligence and interpersonal communication do not show a significant partial effect on performance. However, simultaneously, employee empowerment, intellectual intelligence, and interpersonal communication have a significant influence on the performance of civil servants. The study concludes that employee empowerment is the most influential factor in improving civil servant performance, although other variables also contribute collectively.